Primary cardiac lymphoma presenting as heart failure and atrioventricular block: case report - Liu, Jiyi; Sun, Fengzhi; Jia, Sixun; Zhang, Shulong; Wang, Yu (Frontiers in Oncology, 2025)
Primary cardiac lymphoma (PCL) is an extremely rare and highly aggressive malignancy that typically presents with nonspecific cardiac symptoms. We report a case of primary cardiac diffuse large B-cell lymphoma (DLBCL) with initial manifestations of heart failure and third-degree atrioventricular block. The patient presented with progressive dyspnea, palpitations, and unintentional weight loss. Transthoracic echocardiography revealed a large right atrial mass. The patient first underwent surgical resection of the cardiac tumor, and pathological examination confirmed non-GCB subtype DLBCL. During fractionated R-CHOP chemotherapy, the patient experienced cardiac arrest, necessitating the urgent implantation of a temporary pacemaker. Subsequently, a permanent pacemaker was implanted using a physiological pacing strategy. After six cycles of chemotherapy and ongoing pacing support, the patient achieved complete remission, with no evidence of tumor recurrence during the follow-up period. This case suggests that for PCL patients presenting with heart failure and third-degree atrioventricular block, a combination of surgical resection, fractionated R-CHOP chemotherapy, and physiological pacing may contribute to a favorable outcome.